Prevention of suicide behind bars: first Italian results - Annalisa Frangione; Letizia Bracali; Luca Rosi; Maria Mancino; Marisa Meschi; Nicola Nante; Gianmarco Troiano (Egyptian Journal of Forensic Sciences, 2017)
Abstract Background The reduction of suicides in jails and prisons is an international priority and, after the publication of a report about the necessity to prevent the suicide risk, in Tuscany (Italy) was created a new biphasic protocol. The aim of our study was to show the preliminary results after the introduction of this protocol in the Penitentiary of Pistoia. Methods We conducted an ecological pilot study from April to December 2016. In the Penitentiary of Pistoia, a multidisciplinary staff collected socio-demographic and clinical information of the new inmates, and estimated the suicide risk administering the Arboleda-Florez Checklist. Results Ninety-three new prisoners (all males) were conducted in the Penitentiary of Pistoia: 12 (12.90%) came from another prison; 81 (87.09%) were free before the arrival. 16 (17.2%) were homeless, 52 (55.91%) were unemployed, 1 (1.07%) was retired. 32 declared to use drugs; 7 of them declared also the alcohol abuse. Three detainees claimed only the alcohol abuse. 9 prisoners were already assisted by the Service for Drug Addiction when they have been arrested. 77 (82.79%) were positive for at least 1 item of the Arboleda-Florez Checklist. The measures of great surveillance were disposed for 67 prisoners. Three were the measures of Greatest Surveillance for high suicide risk. 13 inmates needed a specific pharmacological treatment prescribed by a psychiatrist. A therapy for mild anxiety and insomnia was prescribed in 29 cases: 21 after the first visit; 8 later. A psychological support was furnished to 23 prisoners who didn’t need the prescription of psychotropic medication, but only an emotional support. Conclusions Our pilot study showed that the biphasic protocol could be able to manage in a good way the suicide risk, in fact no suicide occurred in the examined period of time. However, studies covering longer periods of time and involving other realities are needed to give more reliable results about its real efficacy.